Envolvimento do polimorfismo da apolipoproteina A1 (rs670) no tamanho e ação antioxidante da lipoproteína de alta densidade - Meneses, Richard Rarison Cavalcante (2023)
Cardiovascular diseases, a non-communicable chronic diseases, is an important cause of death worldwide. There are several risk factors for the development of these heart diseases, including modifiable factors (hypertension, obesity, dyslipidemia, diabetes) and non-modifiable factors (genetics, age, and sex). Non-modifiable factors may influence lipoprotein metabolism, specifically alterations in high-density lipoprotein (HDL) functionality and genetic factors on these functions, mainly genetic polymorphisms. In this context, the single nucleotide polymorphism rs670 of the Apo A1 gene is highlighted, in which the wild-type allele has guanine (G) replaced by adenine (A) in the polymorphic allele. Thus, the objective of this study was to evaluate the involvement of the Apo A1 (rs670) polymorphism in the size and antioxidant action of high-density lipoprotein (HDL). For this purpose, 78 volunteer individuals of both sexes, aged 20 to 75, attending the Laboratory of Clinical and Toxicological Analysis at the Federal University of Ceará, were included. Two groups were constructed according to the presence of the A allele related to the Apo A1 (rs670) gene polymorphism. Data collection included socio-economic, cultural and clinical information, anthropometric analyses, glycolipid profile analyses (glucose, total cholesterol, cholesterol fractions, triglycerides, Apolipoprotein A, Apolipoprotein B, non-esterified fatty acids, omega-3 index) of obtained blood samples; analysis of HDL subfractions (Lipoprint System, Quantrimetrix®); analysis of HDL antioxidant function through lag time assay; and genotyping of the rs670 polymorphism of the ApoA1 gene using the TaqMan system. There was observed no differences in glycolipid and anthropometric profile parameters between the groups concerning the presence or absence of the A allele; glucose, triglycerides, BMI, and waist circumference had an inversely proportional correlation with c-HDL (HDL cholesterol) concentration in individuals without the A allele, but this correlation ceased to exist when the A allele was present; there was a positive correlation between c-HDL concentration and the HDL 1-2/9-10 ratio (concentration of large particles divided by small particles) independent of rs670, but this correlation was stronger (rho=0.827; p=0.001) in individuals carrying the A allele. Glucose and ApoB/ApoA index showed a negative correlation with the HDL 1-2/9-10 ratio in individuals with the A allele; lag time HDL showed no association with rs670 or correlation with anthropometric and glycolipid profile parameters regarding the presence of the A allele. Although there was no association between HDL particle size and the presence of the A allele in a univariate approach, in a multivariate regression analysis, an elevated HDL 1-2/9-10 ratio was independently associated with the presence of the A allele, in the context of glycolipid and anthropometric profile alterations. However, HDL's antioxidant function, analyzed by lag time, showed no association with the presence of the A allele in all regression models. In conclusion, the ApoA1 (rs670) polymorphism appears to have an important influence on the size of HDL particles in the scenario with glycolipid and anthropometric profile alterations.